Risk of Exposure to Trace Elements through the Application of Facial Makeup Powders - Selina Ama Saah; Nathaniel Owusu Boadi; Patrick Opare Sakyi; Godfred Darko; Michael Baah Mensah (Journal of Chemistry)
The study aimed to ascertain the levels of trace elements present in the face powders marketed in Ghana. Fifteen different brands of facial makeup powders were purchased from a local market in Ghana. The samples were analyzed using an X-ray fluorescence (XRF) analyzer to determine the concentrations of 16 elements (Pb, As, Hg, Zn, Fe, Mn, Cr, Ti, Cu, Ni, Co, Sb, Cd, Ag, Sn, and Au). The contents of the trace elements were ordered in the following descending order according to the maximum concentrations: Fe > Zn > Ti > Mn > Cr > Hg > As > Pb > Cu, Ni, Co, Sb, Cd, Ag, Sn, and Au. Pearson correlation statistics showed strong positive relationships between Pb and Zn (r = 0.71), Pb and Cr (r = 0.57), Hg and Zn (r = 0.63), Hg and Fe (r = 0.73), Hg and Cr (r = 0.61), Zn and Fe (r = 0.69), Zn and Cr (r = 0.88), Fe and Cr (r = 0.67), and Fe and Ti (r = 0.62). Except for Pb and Cr, all the other elements had their margin of safety (MOS) values less than 100. The hazard indices (HIs) for Pb, Mn, Cr, and Ti were less than 1, indicating no risk. However, the HIs for As, Hg, Zn, and Fe were more than 1, indicating a potential risk of usage in adults. As a result, using face powders could put users at risk of exposure to trace elements. Dermal exposure to trace elements from cosmetics resulted in a lifetime cancer risk (LCR) that was higher than what was considered tolerable (LCR >10−6) due to the presence of Pb, As, and Cr. Mercury was identified as a potential skin sensitizer in the cosmetic samples examined by an exposure-based sensitization quantitative risk assessment (SQRA).